ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI KEPUTUSAN PEMBELIAN ONLINE - Santoso, Laina Tussifah (Lembaga Kajian Ilmu Sosial dan Politik (LKISPOL), 2024)
This research was carried out to obtain data that shows an overview of the influence of brand, price, promotion on purchasing decisions for e-commerce Tiktok Shop on the street (Batang Kuis Masjid Al Bayan Gang Sejahtera Medan). This research uses a quantitative approach. The type of research used in this research is quantitative research. The population in this research are consumers on Jalan Batang Kuis Gang Masjid Al Bayan Gang Sejahtera Medan. The sample in this study was 40 consumers on Jalan Batang Kuis Gang Masjid Al Bayan Gang Sejahtera Medan. The data sources used are primary and secondary data. Data collection techniques include interviews, filling out questionnaires and observation. The data analysis technique used is hypothesis testing. The research results of brand, price and promotion variables partially have a positive and significant effect on purchasing decisions at the TikTok Shop. Brand, price and promotion simultaneously have a positive and significant influence on purchasing decisions at the TikTok Shop.